Answer:
The answer is 4
Step-by-step explanation:
Solve:
p = 1
q = 1
= (1+1)2 - (5-5)
= 2+2 -5 +5
= 4
Make sure to give me brainliest answer!
6m (m+2) = 0 is the factored form
m=0, m=-2 is m
Steps are on paper
If you need more explanation, comment
A comparison between a function and its inverse would show that the domain and range of the original function swap. The domain of the function becomes the range of the inverse, the range of the function becomes the domain of its inverse.
Looking at ordered pairs of the function and its inverse would look like this:
(2,4) on the original function becomes (4,2) on the inverse.
While the graph of a function and its inverse are noticeably different an important thing to note is that it is merely a reflection across the line y=x.
So even though they appear different you are looking at the same relationship just as y vs. x instead of x vs. y
B=1.4
Is the answer.
This is just for more characters <span />
4 cos² x - 3 = 0
4 cos² x = 3
cos² x = 3/4
cos x = ±(√3)/2
Fixing the squared cosine doesn't discriminate among quadrants. There's one in every quadrant
cos x = ± cos(π/6)
Let's do plus first. In general, cos x = cos a has solutions x = ±a + 2πk integer k
cos x = cos(π/6)
x = ±π/6 + 2πk
Minus next.
cos x = -cos(π/6)
cos x = cos(π - π/6)
cos x = cos(5π/6)
x = ±5π/6 + 2πk
We'll write all our solutions as
x = { -5π/6, -π/6, π/6, 5π/6 } + 2πk integer k